NEW METHOD OF PROFILOMETERS FOR TRIBOSYSTEMS - Кіяшко, С. М.; Стельмах, О. У.; Смірнов, Є. М.; Ільченко, Л. М.; Сидоренко, О. Ю.; Колєнов, С. О.; Костюнік, Р. Є. (Proceedings of National Aviation University (archive), 2021)
It is proved that the roughness of working surfaces and their volumetric configuration in the friction nodes is a very important and sometimes crucial characteristic that significantly affects the efficiency of tribosystems. The laser scanning profilograph-profilometer LSPP-03 is considered, which allows to create the newest industrial technologies of manufacturing of friction surfaces of tribosystems with super-effective tribocharacteristics.